Medicated Feed Additives for Beef Cattle and Calves - Falkner, Thomas R.; Stokka, Gerald L.; Baker, Scott; Herrman, Tim J. (My University, 1997)
This publication explains the regulations regarding the use of medicated feed additives and to provide a list of approved drugs and drug combinations, use levels, and indications for use of medicated feed additives for beef cattle and calves.
MF2043_1997_10
Keywords: MF2043; Livestock; MF